1999
DOI: 10.1210/jcem.84.2.5438
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Alters the Expression and Activity of the Human Placental GLUT1 Glucose Transporter1

Abstract: This study was designed to investigate the effects of maternal diabetes on glucose transporter expression and glucose transport activity in the human placenta. Syncytiotrophoblast microvillous and basal membranes were prepared from placental tissue obtained at term from pregestational diabetics (White class B) and gestational diabetics controlled either by diet alone (class A1) or by diet and insulin (class A2). These membranes were used to measure GLUT1 glucose transporter expression and D-glucose transport a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 54 publications
0
15
0
1
Order By: Relevance
“…GDM is associated with altered placental glucose metabolism (Osmond et al 2001, Jansson & Powell 2006 and altered amino acid transport (Jansson et al 2002) and lipid (Segura et al 2017) concentrations. Consequentially, GDM trophoblasts exhibit a two-fold increase in GLUT-1 expression and 40% increase in glucose uptake in the trophoblast basal membrane (Gaither et al 1999). These observed changes in GLUT-1 expression may potentially increase glucose uptake from the maternal circulation into the basal membrane.…”
Section: Placental Dysfunctionmentioning
confidence: 98%
“…GDM is associated with altered placental glucose metabolism (Osmond et al 2001, Jansson & Powell 2006 and altered amino acid transport (Jansson et al 2002) and lipid (Segura et al 2017) concentrations. Consequentially, GDM trophoblasts exhibit a two-fold increase in GLUT-1 expression and 40% increase in glucose uptake in the trophoblast basal membrane (Gaither et al 1999). These observed changes in GLUT-1 expression may potentially increase glucose uptake from the maternal circulation into the basal membrane.…”
Section: Placental Dysfunctionmentioning
confidence: 98%
“…Glucose transport capacity seems to be increased in GDM placentas, but with conflicting results about GLUT1 expression and activity in MVM and BM (24). At the same time, it has been demonstrated that women with Type 1 Diabetes (T1D) and first trimester hyperglycemia, showed higher expression of GLUT1 in the BM compared to healthy pregnancies (27).…”
Section: Placenta: a Metabolic Organmentioning
confidence: 99%
“…Contrasting findings in the literature could be related to mouse strain or timepoint of investigation, as well as mode and severity of diabetes. In human pregnancies with pre-gestational diabetes, SLC2A1/GLUT1 expression was found increased in term placenta [27], specifically in basal membrane preparations [28, 29]; however, the much longer pregnancy in human precludes a direct comparison to rodent pregnancies. Overall, our finding of increased placental Slc2a1/Glut1 expression over time in mouse placenta conforms to previous reports for human placental SLC2A1/GLUT1 expression [30], for sheep pregnancy [31, 32] and for rat [24] and mouse [33, 34].…”
Section: Discussionmentioning
confidence: 99%